An injection molded nanocrystalline magnetic core and a preparation method thereof

By performing the injection molding process in a mixed slurry of nanocrystalline soft magnetic alloy powder and epoxy-based modified silicone resin adhesive, the problem in the prior art is solved that it is difficult to achieve good insulation coating by conventional injection molding and adhesive under low content conditions, and the effect of efficient preparation of high-performance nanocrystalline magnetic cores is achieved.

CN119742143APending Publication Date: 2025-04-01SHENZHEN YN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411934291.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art is difficult to prepare nanocrystalline magnetic cores through conventional injection molding, and low-melting glass adhesives cannot achieve good insulation coating under low content conditions, resulting in a reduction in high-frequency magnetic performance.

Method used

A mixed slurry of nanocrystalline soft magnetic alloy powder and epoxy modified silicone resin adhesive was prepared by injection molding process, and the nanocrystalline powder was surface modified with aminosilane coupling agent to improve the bonding and curing and insulating coating effect.

Benefits of technology

It has achieved nanocrystalline magnetic cores with high magnetic powder content and high magnetic properties under low adhesive resin content, which are suitable for conventional injection molding and processing, and have excellent filtering effects in new energy vehicles and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742143A_ABST
    Figure CN119742143A_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of soft magnetic materials and new energy vehicles, and specifically relates to an injection-molded nanocrystalline magnetic core and a preparation method thereof. The nanocrystalline magnetic core comprises a plastic part and a nanocrystalline magnetic powder core arranged inside the plastic part; the nanocrystalline magnetic powder core is obtained by injection molding a mixed slurry of nanocrystalline soft magnetic alloy powder and an adhesive. The nanocrystalline magnetic powder core of the present invention is obtained by injection molding a mixed slurry of nanocrystalline soft magnetic alloy powder and an adhesive, and has the characteristics of simple molding process, small volume, good filtering effect and convenience for subsequent power supply assembly. By further adopting a specific epoxy-modified silicone resin adhesive, the bonding curing and insulation coating of the magnetic powder can be achieved under a lower adhesive resin content, and a product with a high magnetic powder content and high magnetic properties can be obtained under a lower molding pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of soft magnetic materials, and in particular relates to an injection-molded nanocrystalline magnetic core and a preparation method thereof. Background Art

[0002] At present, the materials used to prepare magnetic cores mainly include ferrite soft magnetic materials, iron alloy soft magnetic materials, amorphous / nanocrystalline soft magnetic materials and composite soft magnetic materials. Ferrite has good magnetic permeability and low magnetic resistance, which can greatly improve the efficiency of power inductors. However, its saturation magnetic induction intensity is relatively small, which limits the preparation of miniaturized and lightweight products. Iron alloy soft magnetic materials have high saturation magnetic induction intensity, but the loss is large at high frequencies. Amorphous / nanocrystalline soft magnetic materials have broad application prospects in the preparation of magnetic cores because of their high saturation magnetic induction intensity and low high-frequency loss. However, amorphous / nanocrystalline materials have the defects of being fragile and poor in flexibility. In actual processing, they are generally used in thin strip materials with a thickness of less than 40μm, which is difficult to meet the processing and molding requirements of magnetic core products.

[0003] Patent CN 1579682A discloses an amorphous soft magnetic core with excellent high-frequency characteristics, which is obtained by the following steps: heat-treating an iron-based amorphous metal ribbon made by RSP and then converting it into a nano-grained metal ribbon; rolling the nano-grained metal ribbon to obtain a nano-grained metal powder; classifying the nano-grained metal powder and then mixing it into a powder particle distribution with an optimal uniform composition; mixing the mixed nano-grained metal powder with a binder and then forming it into a magnetic core; and annealing the formed magnetic core and then coating the magnetic core with an insulating resin. Although the prior art prepares an amorphous soft magnetic core by mixing a nano-crystalline ribbon with a binder after powdering, the binder used is a low-melting-point glass, which needs to be pressed and formed under a relatively high pressure and cannot be applied to conventional injection molding. Moreover, the binder cannot achieve a good insulating coating effect when the content is less than 1.5wt%, resulting in reduced high-frequency magnetic properties. Summary of the invention

[0004] In view of the shortcomings and deficiencies of the above prior art, the primary purpose of the present invention is to provide an injection-molded nanocrystalline magnetic core.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned integrally injection-molded nanocrystalline magnetic core.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] An injection-molded nanocrystalline magnetic core comprises a plastic part and a nanocrystalline magnetic powder core arranged inside the plastic part; the nanocrystalline magnetic powder core is obtained by injection molding a mixed slurry of nanocrystalline soft magnetic alloy powder and an adhesive.

[0008] Furthermore, the nanocrystalline magnetic powder core includes but is not limited to closed shapes such as annular, racetrack, and rectangular.

[0009] Furthermore, the nanocrystalline magnetic powder core is a stack of one or more short magnetic powder cores, and adjacent short magnetic powder cores are separated by hard spacers; the material of the hard spacers is aluminum alloy, iron alloy or plastic. More preferably, multiple short magnetic powder cores are stacked, and the loss can be further reduced by stacking multiple short magnetic powder cores.

[0010] Furthermore, a hard shell for protection is also provided outside the plastic part, and the material of the hard shell is aluminum alloy, iron alloy or plastic.

[0011] Furthermore, the composition system of the nanocrystalline soft magnetic alloy powder is Fe bal. M a Cu b M' c Si d B e X f , wherein M is Co and / or Ni, M' is at least one of Nb, V, Ta, and Mo, and X is at least one of common impurity elements such as C, O, N, S, and P; a=0-30%, b=0-2%, c=0-7%, d=5-18%, e=5-15%, and f=0-0.5%.

[0012] Furthermore, the D50 particle size of the nanocrystalline soft magnetic alloy powder is 5 to 150 μm.

[0013] Further preferably, the nanocrystalline soft magnetic alloy powder is a nanocrystalline soft magnetic alloy powder surface-modified with an aminosilane coupling agent.

[0014] Furthermore, the adhesive is epoxy resin, polyurethane resin, silicone resin or polyacrylate resin.

[0015] Further preferably, the adhesive is an epoxy-modified silicone resin, which is prepared by the following method:

[0016] The hydrogen-containing silicone oil, allyl glycidyl ether and an organic solvent are mixed evenly, and then a chloroplatinic acid isopropanol solution catalyst is added to heat and react to obtain an epoxy-modified silicone resin adhesive.

[0017] Preferably, the hydrogen-containing silicone oil is a hydrogen-containing silicone oil having a number average molecular weight of 1000 to 10000 and a hydrogen content of 0.2 to 1 wt.%.

[0018] Preferably, the amount of allyl glycidyl ether used is 5% to 30% of the mass of the hydrogen-containing silicone oil.

[0019] Preferably, the organic solvent is one or more of N,N-dimethylformamide, toluene, xylene, ethyl acetate, butyl acetate, n-hexane, n-heptane, acetone, butanone, tetrahydrofuran, and isopropanol; and the amount of the organic solvent used is 5% to 20% of the total mass of the hydrogen-containing silicone oil and allyl glycidyl ether.

[0020] Preferably, the heating reaction is carried out at a temperature of 70 to 90° C. and for a time of 1 to 6 hours.

[0021] Furthermore, the mass ratio of the nanocrystalline soft magnetic alloy powder to the adhesive is 80-99.5:0.5-20; more preferably 99-99.5:0.5-1.

[0022] The method for preparing the above-mentioned integrally injection-molded nanocrystalline magnetic core comprises the following preparation steps:

[0023] The plastic part is injection molded in a mold, and then a mixed slurry of nanocrystalline soft magnetic alloy powder and adhesive is injected, and dried and solidified at a pressure of 0 to 50 MPa and a temperature of 60 to 120° C. to obtain a nanocrystalline magnetic core.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The nanocrystalline magnetic core of the present invention is obtained by injection molding a mixed slurry of nanocrystalline soft magnetic alloy powder and adhesive, and has the characteristics of simple molding process, small volume, good filtering effect and convenience for subsequent power supply assembly. The most typical application scenario is the electric drive circuit of new energy vehicles. In addition, the magnetic rings of OBC, DC-DC and other power supply components and EMI suppression components such as photovoltaics and communication power supplies can also refer to this product design.

[0026] (2) The nanocrystalline magnetic core of the present invention further adopts nanocrystalline soft magnetic alloy powder whose surface is modified by aminosilane coupling agent and specific epoxy-modified silicone resin adhesive through injection molding, which can realize bonding curing and insulation coating of magnetic powder under low adhesive resin content, and can obtain products with high magnetic powder content and high magnetic properties under low molding pressure. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the structure of the injection-molded nanocrystalline magnetic core obtained in Example 1;

[0028] Figure 2 Schematic diagram of the structure of the combination of the injection-molded nanocrystalline magnetic core, the copper busbar and the hard shell obtained in Example 1;

[0029] Figure 3 Schematic diagram of the structure of the injection-molded nanocrystalline magnetic core obtained in Example 5;

[0030] Figure 4 Schematic diagram of the structure of the injection-molded nanocrystalline magnetic core obtained in Example 6. DETAILED DESCRIPTION

[0031] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0032] Example 1

[0033] (1) The composition is Fe 73.5 Cu1Nb3Si 15.5 The iron-based amorphous alloy with a particle size of B7 (at.%) was prepared into a powder with a D50 particle size of 45 μm by water-gas combined atomization, and then heated to 580° C. for annealing and crystallization treatment for 3 h to obtain nanocrystalline soft magnetic alloy powder.

[0034] (2) By weight, 90 parts of nanocrystalline soft magnetic alloy powder and 10 parts of epoxy resin glue were mixed evenly by high-speed stirring, and then injected into the injection-molded plastic part. After applying a pressure of 30 MPa, the temperature was raised to 100°C for drying and curing for 15 minutes, and then placed at 75°C for 24 hours and cooled to room temperature to obtain an integrally injection-molded nanocrystalline magnetic core. The structural schematic diagram of the obtained integrally injection-molded nanocrystalline magnetic core is shown in FIG. Figure 1 The schematic diagram of its structure combined with the copper busbar and hard shell is shown in Figure 2 shown.

[0035] Example 2

[0036] Compared with Example 1, the method for preparing the integrally injection-molded nanocrystalline magnetic core adopts 95 parts of nanocrystalline soft magnetic alloy powder and 5 parts of epoxy resin glue for mixed injection molding, and the rest is the same.

[0037] Example 3

[0038] Compared with Example 1, the method for preparing the integrally-injected nanocrystalline magnetic core adopts 99 parts of nanocrystalline soft magnetic alloy powder and 1 part of epoxy resin glue for mixed injection molding, and the rest is the same.

[0039] Example 4

[0040] Compared with Example 1, the method for preparing the integrally injection-molded nanocrystalline magnetic core adopts 99.5 parts of nanocrystalline soft magnetic alloy powder and 0.5 parts of epoxy resin glue for mixed injection molding, and the rest is the same.

[0041] Example 5

[0042] (1) The composition is Fe 73.5 Cu1Nb3Si 15.5 The iron-based amorphous alloy with a particle size of B7 (at.%) was prepared into a powder with a D50 particle size of 45 μm by water-gas combined atomization, and then heated to 580° C. for annealing and crystallization treatment for 3 h to obtain nanocrystalline soft magnetic alloy powder.

[0043] (2) By weight, 99 parts of nanocrystalline soft magnetic alloy powder and 1 part of epoxy resin glue were mixed evenly by high-speed stirring, and then injected into the injection-molded plastic parts in two batches. After applying a pressure of 30MPa, the temperature was raised to 100°C for drying and curing for 15 minutes. The adjacent two layers of cured magnetic cores were separated by a plastic hard spacer, and then placed at 75°C for 24 hours and cooled to room temperature to obtain an integrally injection-molded nanocrystalline magnetic core with two short magnetic cores stacked. The structural schematic diagram of the obtained integrally injection-molded nanocrystalline magnetic core is shown in FIG. Figure 3 shown.

[0044] Example 6

[0045] (1) The composition is Fe 73.5 Cu1Nb3Si 15.5 The iron-based amorphous alloy with a particle size of B7 (at.%) was prepared into a powder with a D50 particle size of 45 μm by water-gas combined atomization, and then heated to 580° C. for annealing and crystallization treatment for 3 h to obtain nanocrystalline soft magnetic alloy powder.

[0046] (2) According to the mass percentage, 99.5 parts of nanocrystalline soft magnetic alloy powder and 0.5 parts of epoxy resin glue were mixed evenly by high-speed stirring, and then injected into the injection-molded plastic parts in three batches. After applying a pressure of 30MPa, the temperature was raised to 100°C for drying and curing for 15 minutes. The two adjacent layers of cured magnetic were separated by a plastic hard spacer, and then placed at 75°C for 24 hours and cooled to room temperature to obtain an integrally injection-molded nanocrystalline magnetic core with three short magnetic cores stacked. The structural schematic diagram of the obtained integrally injection-molded nanocrystalline magnetic core is shown in FIG. Figure 4 shown.

[0047] Example 7

[0048] The method for preparing the integrally injection-molded nanocrystalline magnetic core is as follows: Compared with Example 3, the nanocrystalline soft magnetic alloy powder is surface-modified by the following method:

[0049] The nanocrystalline soft magnetic alloy powder and a 5% by mass 3-aminopropyltrimethoxysilane isopropanol solution were stirred and mixed evenly, the amount of 3-aminopropyltrimethoxysilane added was 0.5% of the mass of the magnetic powder, the temperature was raised to 50°C for stirring reaction, and after the reaction was completed, vacuum was evacuated and the temperature was raised to 80°C for drying to obtain a nanocrystalline soft magnetic alloy powder surface-modified with an aminosilane coupling agent.

[0050] Example 8

[0051] The method for preparing the integrally injection-molded nanocrystalline magnetic core is similar to that of Example 7, except that an equal amount of epoxy-modified organic silicone resin adhesive is used to replace the epoxy resin adhesive, and the rest of the steps are the same.

[0052] The epoxy-modified silicone resin glue is prepared by the following method:

[0053] By mass, 100 parts of hydrogen-containing silicone oil with a number average molecular weight of 5600 and a hydrogen content of 0.52wt.%, 20 parts of allyl glycidyl ether and 10 parts of toluene were mixed, and a chloroplatinic acid isopropanol solution catalyst with a platinum content of 50ppm was added under nitrogen protection, heated to 80°C and stirred for reaction for 4 hours to obtain an epoxy-modified silicone resin adhesive.

[0054] The relative magnetic permeability (100kHz) and loss (Pcv, 100kHz & 0.2T) of the nanocrystalline magnetic core obtained in the above embodiment were tested, and the results are shown in Table 1 below.

[0055] Table 1

[0056] Test Group Magnetic Permeability <![CDATA[Loss (W / cm 3 )]]> Example 1 107 1.85 Example 2 126 1.56 Example 3 145 1.82 Example 4 148 2.57 Example 5 141 1.48 Example 6 139 1.56 Example 7 152 1.20 Example 8 164 0.85

[0057] According to the results of Examples 1 to 4 in Table 1, it can be seen that with the increase of the content of nanocrystalline soft magnetic alloy powder and the decrease of the content of epoxy resin glue, the magnetic permeability of the obtained magnetic core shows an increasing trend, and the loss shows a trend of first decreasing and then increasing. The reason is that the increase of the content of soft magnetic alloy powder will increase the density of the magnetic core, thereby increasing the magnetic permeability; but too low epoxy resin adhesive will lead to poor insulation coating effect and poor bonding curing effect, thereby increasing the loss. It can be seen from the comparison results of Example 3 and Example 5 and Example 4 and Example 6 that the superposition of multiple short magnetic cores can significantly reduce the loss compared with a single integral magnetic core. It can be seen from the comparison results of Example 3 and Example 7 that the nanocrystalline soft magnetic alloy powder surface-modified by aminosilane coupling agent can produce chemical bonding with epoxy resin, thereby improving the insulation coating effect and bonding curing effect, and to a certain extent, improving the magnetic permeability of the magnetic core and significantly reducing the loss. It can be seen from the comparison results of Example 7 and Example 8 that the use of specific epoxy-modified silicone resin adhesive instead of epoxy resin adhesive can further improve the insulation coating effect and the bonding and curing effect, further increase the magnetic permeability of the magnetic core and reduce the loss.

[0058] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An injection molded nanocrystalline magnetic core, characterized in that: It comprises a plastic part and a nanocrystalline magnetic powder core arranged inside the plastic part; the nanocrystalline magnetic powder core is obtained by injection molding a mixed slurry of nanocrystalline soft magnetic alloy powder and adhesive.

2. The injection molded nanocrystalline magnetic core according to claim 1, characterized in that: The nanocrystalline magnetic powder core is in a ring-shaped, racetrack-shaped or rectangular closed shape.

3. The injection molded nanocrystalline magnetic core according to claim 1, characterized in that: The nanocrystalline magnetic powder core is a stack of one or more short magnetic powder cores, and adjacent short magnetic powder cores are separated by hard spacers; the material of the hard spacers is aluminum alloy, iron alloy or plastic.

4. The injection molded nanocrystalline magnetic core according to claim 1, characterized in that: A hard shell for protection is also arranged outside the plastic part, and the material of the hard shell is aluminum alloy, iron alloy or plastic.

5. The injection molded nanocrystalline magnetic core according to claim 1, characterized in that: The composition system of the nanocrystalline soft magnetic alloy powder is Fe bal. M a Cu b M' c Si d B e X f , wherein M is Co and / or Ni, M' is at least one of Nb, V, Ta, and Mo, and X is at least one of common impurity elements such as C, O, N, S, and P; a=0-30%, b=0-2%, c=0-7%, d=5-18%, e=5-15%, and f=0-0.5%.

6. The injection molded nanocrystalline magnetic core according to claim 5, characterized in that: The D50 particle size of the nanocrystalline soft magnetic alloy powder is 5 to 150 μm.

7. The injection molded nanocrystalline magnetic core according to claim 1, characterized in that: The nanocrystalline soft magnetic alloy powder is a nanocrystalline soft magnetic alloy powder surface-modified by an aminosilane coupling agent.

8. The injection molded nanocrystalline magnetic core according to claim 1, characterized in that: The adhesive is epoxy resin, polyurethane resin, silicone resin or polyacrylate resin.

9. The injection molded nanocrystalline magnetic core according to claim 7, characterized in that: The adhesive is an epoxy-modified silicone resin, which is prepared by the following method: The hydrogen-containing silicone oil, allyl glycidyl ether and an organic solvent are mixed evenly, and then a chloroplatinic acid isopropanol solution catalyst is added to heat and react to obtain an epoxy-modified silicone resin adhesive.

10. The injection molded nanocrystalline magnetic core according to claim 9, characterized in that: The hydrogen-containing silicone oil has a number average molecular weight of 1000-10000 and a hydrogen content of 0.2-1 wt. %; the amount of allyl glycidyl ether used is 5%-30% of the mass of the hydrogen-containing silicone oil.

11. The injection molded nanocrystalline magnetic core according to claim 9, characterized in that: The organic solvent is one or more of N,N-dimethylformamide, toluene, xylene, ethyl acetate, butyl acetate, n-hexane, n-heptane, acetone, butanone, tetrahydrofuran, and isopropanol; the amount of the organic solvent is 5% to 20% of the total mass of the hydrogen-containing silicone oil and allyl glycidyl ether.

12. The injection molded nanocrystalline magnetic core according to claim 9, characterized in that: The temperature of the heating reaction is 70-90° C. and the time is 1-6 hours.

13. The injection molded nanocrystalline magnetic core according to claim 1, characterized in that: The mass ratio of the nanocrystalline soft magnetic alloy powder to the adhesive is 80-99.5:0.5-20.

14. The injection molded nanocrystalline magnetic core according to claim 9, characterized in that: The mass ratio of the nanocrystalline soft magnetic alloy powder to the adhesive is 99-99.5:0.5-1.

15. The method for preparing an injection-molded nanocrystalline magnetic core according to any one of claims 1 to 14, characterized in that: The method comprises the following preparation steps: The plastic part is injection molded in a mold, and then a mixed slurry of nanocrystalline soft magnetic alloy powder and adhesive is injected, and dried and solidified at a pressure of 0 to 50 MPa and a temperature of 60 to 120° C. to obtain a nanocrystalline magnetic core.